2014
DOI: 10.4018/ijaeis.2014040103
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Biomass and Nitrogen Status in Wheat Crop by Spectral Reflectance Using Artificial Neural Networks

Abstract: Precision Agriculture has the goal of reducing cost which is difficult when it is related to fertilizers application. Nitrogen (N) is the nutrient absorbed in greater amounts by crops and the N fertilizers application present significant costs. The use of spectral reflectance sensors has been studied to identify the nutritional status of crops and prescribe varying N rates. This study aimed to contribute to the determination of a model to discriminating biomass and nitrogen status in wheat through two sensors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Based on the regression equation for grain yield (Fig. 2b) Since the soil N availability is dependent on mineralization of organic matter [5] and due to the essential role of N in high-yield systems [7], positive effects of N fertilization on wheat yields have been frequently observed in studies conducted on Brazilian soils [11,17,28]. In our study conducted on an Oxisol with 35 g dm −3 of organic matter in the topsoil (Table 1), a rate of 55 kg N ha −1 for wheat cultivar Quartzo following soybean provided a maximum economic return to obtain grain yield of 4250 kg ha −1 .…”
Section: Effect Of N Fertilization On Wheat Shoot Dry Matter and Graimentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the regression equation for grain yield (Fig. 2b) Since the soil N availability is dependent on mineralization of organic matter [5] and due to the essential role of N in high-yield systems [7], positive effects of N fertilization on wheat yields have been frequently observed in studies conducted on Brazilian soils [11,17,28]. In our study conducted on an Oxisol with 35 g dm −3 of organic matter in the topsoil (Table 1), a rate of 55 kg N ha −1 for wheat cultivar Quartzo following soybean provided a maximum economic return to obtain grain yield of 4250 kg ha −1 .…”
Section: Effect Of N Fertilization On Wheat Shoot Dry Matter and Graimentioning
confidence: 99%
“…3). NDVI variations depending on the level of N fertilization are usually fitted by linear or quadratic equations [1,11]. Although wheat shoot dry matter and grain yields at physiological maturation were not affected by the level of N fertilization at sowing, the NDVI values showed that N fertilization at sowing favored the early growth of wheat plants.…”
Section: Effect Of Sensor Height On Wheat Spectral Reflectance Measurmentioning
confidence: 99%